Mitos Tumbuhan Medis sebagai Simbol Bahan Narkotika dalam Film Dokumenter - Muhammad Aldy Febiansyah; Firmansyah; Dadi Ahmadi (Jurnal Riset Jurnalistik dan Media Digital, 2023)
Abstract. The film How To Change Your Mind is a film whose title explains that we have to change our thinking when watching this film. This film tells about how Michael Pollan and also the narrator in the film tell and explain how psychedelics change our minds. Psychedelic which means "Mind Manifestation" is an effect or condition when we try substances that have psychedelic effects or are now included in class I narcotics. This research takes data from the documentary series How To Change Your Mind which is based on a book entitled How To Change Your Mind by Michael Pollan. This film tells how psychedelic effects occurred in the past and the impact we can still feel today. Uniquely, this psychedelic was banned due to a problematic CIA mind control experiment, while this psychedelic can help someone get out of someone's suicidal ideation. The research aims to examine what meanings are related to informative messages from the meaning of semiotics. This study uses a qualitative approach to Roland Barthes' semiotic analysis in the film How To Change Your Mind. By analyzing the denotative, connotative and mythical signs taken from this film, the researcher found the research results in the form of data taken by observing the film through scenes or scenes, dialogues, background music used in the film to some of the characters involved. Abstrak. Film How To Change Your Mind merupakan film yang judulnya menjelaskan bahwa kita harus merubah pemikiran kita ketika menonton film ini. Film ini menceritakan tentang bagaimana Michael Pollan dan juga narator dalam film tersebut menceritakan serta menejelaskan bagaimana psikedelik merubah pikiran kita. Psikedelik yang mempunyai arti “Manifestasi Pikiran” merupakan efek atau keadaan saat kita mencoba zat-zat yang memiliki efek psikedelik atau sekarang dimasukan kedalam narkotika golongan I. Penelitian ini mengambil data dari film series dokumenter How To Change Your Mind yang diangkat berdasarkan buku yang berjudul How To Change Your Mind oleh Michael Pollan. Film ini menceritkan bagaimana efek psikedelik terjadi di masa lampau dan dampaknya yang sampai sekarang masih bisa kita rasakan. Uniknya psikedelik ini dilarang akibat ekperimen pengendalian pikiran CIA yang bermasalah sedangkan psikedelik ini dapat membantu seseorang keluar dari keingingan bunuh diri yang dialamai seseorang. Penelitian bertujuan untuk meneliti makna apa saja yang berkaitan dengan pesan informatif dari sisi pemaknaan semiotika. Penelitian ini menggunakan metodologi pendekatan kualitatif analisis semiotika Roland Barthes dalam film How To Change Your Mind. Dengan menganalisis tanda denotatif, konotatif serta mitos yang diambil dari film ini, peneliti menemukan hasil penelitian berupa data yang diambil dengan cara observasi film melalui scene atau adegan, dialog, latar musik yang digunakan dalam film tersebut kepada beberapa tokoh yang terlibat.